A formação em contexto na educação integral do ponto de vista dos professores de uma escola pública: uma análise da dialogicidade no processo educativo - Mascioli, Dilene Aparecida Amicci (Universidade Federal de São Carlos, 2019)
This research aims to investigate the conceptions that point to the understanding of teachers who work in an institution of Integral Education and who are involved in context training on dialogicity in the educational process. It is a participant research and qualitative and interpretive nature. We are based on a theoretical framework on Continuing Training and Context Training, in the current legislation: LDB 9394/96, ECA, the Federal Constitution of 1988 and the National Curriculum Guidelines for teacher training (DCNFP - Res. 02/2015). This proposal is in agreement with Freire (2005) and, defined in this research for Integral Education, as a dialectical and problematizing process, because the dialogical perspective allows us to reflect, evaluate, program, investigate and transform specificities of human beings in and with the world. The dialogue, according to Freire (2005) is a method of building emancipatory socio-cultural processes in search of a more humanized world and for Bohm (2005), is a network of coexistence. The study consisted of a Cycle of six Continuous Training Meetings, during the months of October to December 2018, in a municipal school in the interior of São Paulo. Ten teachers and the director were subjects of the research and, working with the researcher at HTPC - Collective Pedagogical Work Schedule. The data were grouped into three categories, entitled thematic axes: 1. Communication and dialogue; 2. Training and professional development and 3. Reflexive practice. We are guided through the Thematic Axes, built and inspired by Bardin (1977), on the categorizations of content analysis, to analyze our research. In general, the data analyzed allowed us to conclude that the understandings attributed by teachers to context training meetings in htpcs are related to a set of factors such as: peer dialogue, understanding of the path of teacher and professional development, reflection of pedagogical practices present in the context of Integral Education in relation to pedagogical discussions and what arises from the new conversational flow. According to the data, the actions are reflective in htpcs, because a process of study of daily life, reflection, observation and discussion about practice provides for new ways to act and print their knowledge throughout the teaching career.
Context training in comprehensive education from the point of view of teachers of a public school: an analysis of dialogicity in the educational process
Keywords: Educação integral; Horário de trabalho pedagógico coletivo; Processo dialógico; Formação em contexto de professores; Prática reflexiva; Integral education; Teacher context training; Collective pedagogical working hours;; Dialogical process; Reflective practice; CIENCIAS HUMANAS